The Effect of Service Quality and Product Price on Consumer Repurchase Intention at Lazatto Chicken & Burger, Pongtiku Branch, Makassar City - Jeni Dina Kristina; Muhammad Jufri; Mahmuddin Mahmuddin; Asmayanti Asmayanti; Pahrul Pahrul (Journal of Innovative and Creativity, 2026)
This study aims to determine the extent of influence of service quality and product price, both partially and simultaneously, on consumer repurchase intention at Lazatto Chicken & Burger, Pongtiku Branch, Makassar City. This study used a descriptive quantitative approach with a survey method by distributing questionnaires to 81 respondents. This study used non-probability sampling with an accidental sampling technique. Data analysis used classical assumption tests with normality tests, hypothesis tests with multiple linear regression, and coefficient of determination tests, using SPSS version 27.0 software. The results showed that service quality and product price had a positive and significant effect on repurchase intention, both partially and simultaneously. These findings confirm that improving service and pricing in line with customer perceptions of value are important factors in building consumer loyalty in the fast food restaurant sector. The R-squared value was 0.520, meaning that 52% of the variation in repurchase intention is explained by service quality and product price. The remaining 42% is explained by variables other than the two independent variables used in the study.